Optimizing Instagram Engagement Strategies for Sustainable Tourism: A Case Study of Ciburial Village - Yudaninggar, Kartika Sari; Damastuti, Riski (Universitas Ahmad Dahlan, 2023)
The aim of this study is to explore the Instagram content management within Ciburial Village, a thriving tourist destination in Bandung Regency, West Java. In the evolving landscape of sustainable tourism, the role of social media platforms, especially Instagram, is pivotal in shaping the narratives of tourist destinations. This study utilizes quantitative content analysis by scrutinizing 134 Instagram uploads from 2021 to unravel the patterns of photo and video uploads, caption messaging, geotagging, and hashtag usage. The findings reveal a preference for photo uploads, predominantly showcasing the vibrant activities of Ciburial Village. Informative captions, while prevalent, lack persuasive elements that can enhance user engagement. The analysis highlights a limited utilization of interactive features, leading to a low engagement rate, a crucial metric for evaluating online presence. Notably, the study identifies the sparse interaction with other accounts and the predominant use of branded hashtags contributing to the account's engagement challenges. The study underscores the importance of fostering a user-centric approach in Instagram content management. Encouraging active participation from followers in content creation and caption ideation can stimulate increased interaction and bolster community bonds. The research contributes significantly to enhance engagement, nurture a vibrant online community, and contribute significantly to sustainable tourism practices by adopting a more inclusive and participatory strategy.